Relative superiority analysis of Garut dam and its crossbred - I Inounu; Subandriyo .; B Tiesnamurti; N Hidajati; La Ode Nafiu (Jurnal Ilmu Ternak dan Veteriner, 2005)
In attemp to increase the productivity of Garut sheep, Indonesian Research Institute for Animal Production has crossed Garut sheep (GG) with St. Croix sheep (HH) that has high frame body size and adaptable to the hot climate (in 1995) and with Moulton Charollais sheep (MM) that has high body weight gain and good milk production to raise multiple birth (in 1996). The objective of this research was to evaluate the ewe productivity of Garut sheep and its crosses with St. Croix and Moulton Charollais. This research was conducted at Animal Research Station, Bogor from 1995 to 2002. In this study the crossing was done using frozen semen of M. Charollais and ram of St. Croix so that the real performance of these sheep under Indonesian condition is not known. So that the relative superiority of these crosses is calculated from the percentage of the differences between traits mean of crossbred and purebred divided by trait means of purebred Garut, except for the threeway crosses (MHG and HMG) is calculated from the difference between the means of threeway crossbred trait with the means of two parents (MG and HG). It is concluded that HG and MHG show higher dam productivity than GG, it can be seen from their litter weight at birth and weaning. In poor feed condition GG showed higher productivity than the crossbred sheep (MG and HG), but MHG/MHG showed higher relative superiority compare to their parents (MG and HG). In good feed condition HG and MHG/HMG sheep showed higher productivity than Garut sheep. The relative superiority of HG sheep is 26.40% over GG and for MHG/HMG is 11.24% over their parents (MG and HG).       Key Words: Garut Sheep, St. Croix Sheep, M. Charollais Sheep, Relative Superiority